Ekplorasi Penentuan Lokasi Tangkap Perikanan Nelayan Bubu Tradisional Desa Assilulu Menggunakan Teknologi Fish Finder - Agung K. Henaulu; Achmad Jais Ely (Jurnal Airaha, 2019)
The objective of this reserach was exploration to determine the location of fishing for for traditional Bubu fishermen by utilizing fishfinder technology. The method used in this research is descriptive exploration, obtained from interviews and field surveys. The sample locations are determined according to the distribution of fishing locations. Currently the traditional bubu fishermen in the village of Assilulu still use traditional tools as a pot in determining and finding the presence of fish to be caught, so that the productivity of the fish produced is not optimal, even though the source of fish in the waters of Assilulu is very abundant. So we need tools that can meet the productivity of responsiveness. Exploration results from 6 different locations with depth variations of 30-60 meters show comparisons from the point of view of fishermen and the use of fishfinder technology there are very different observations. the level of species diversity is in the position of the moderate index with a range of 1 ≤ H ’≤ 3. While in the uniformity index, all regions are included in the index high uniformity criteria between 0.73 - 0.82 and 0.78 - 0.92. For the dominance index, the index range is between 0.142 - 0.306 and 0.125 - 0.178. Then all fishing areas have low dominance, stable, and no ecological pressure. Functional fish diagrams show that the highest target fish fall at the pulpit and Nusi Hena fishing locations, with a percentage value of 19% each.